Pemberian Diary Pada Pasien Anak Dengan Thalasemia Untuk Mengurangi Kecemasan di RSUD Temanggung - Febrianti, Trie; Yuniarti, Falasifah (Universitas Muhammadiyah Yogyakarta, 2023)
Background: Thalassemia is an autosomal recessive hereditary disease, where hemoglobin synthesis is impaired as a result of decreased production of one or more globin chains. Patients with mild thalassemia or called thalassemia minor and intermedia do not need routine blood transfusions, whereas patients with thalassemia major must have blood transfusions routinely and regularly. Treatment of thalassemia patients is carried out using a palliative approach to prevent new problems from occurring, relieve them, improve quality of life, and reduce anxiety for patients and their families. Writing in a diary is known to reduce anxiety. Research Objectives: This study was conducted to analyze the effect of giving a diary to pediatric patients with thalassemia to reduce anxiety in Temanggung Hospital. Research Methods: This research uses qualitative methods. This research was conducted using a case study approach by comparing existing theories. Cases managed were one patient diagnosed with thalassemia. The research process begins with physical assessment and examination of patients, analyzing nursing problems, determining problem priorities, making nursing care plans, implementing, and evaluating. Research Results: There are 4 nursing problems that arise in the case, in this case the researcher implements each problem based on evidence based nursing. However, in this case the researchers focused on discussing anxiety issues by providing diary interventions to reduce anxiety in children with thalassemia. The results of nursing care carried out for 2 days for 45 minutes found that diary administration therapy could reduce the patient's anxiety level. Conclusion: The nursing care carried out is in accordance with the theoretical review and its implementation results in an improvement in the patient's condition. Suggestions for future researchers need to follow up on the results of this final scientific work to assess the effect of giving a diary and assessing the anxiety level of children with thalassemia